Seventeen cases of primary hyperparathyroidism in pregnancy: a call for management guidelines - Di,Marco A; Meeran,K; Christakis,I; Sodhi,V; Nelson-Piercy,C; Tolley,N; Palazzo,F (Journal of the Endocrine Society, 2019)
IntroductionThe risks of primary hyperparathyroidism (pHPT) to pregnant women and their fetuses are well-reported and appear to increase commensurate with serum calcium. The management strategy of pHPT must be adapted in pregnancy and should reflect the severity of hypercalcaemia. However, no guidelines exist to assist clinicians facing this dilemma.MethodsThe experience of a high-volume multidisciplinary endocrine surgical service in managing a consecutive series of pregnant women with pHPT referred for parathyroidectomy is presented and compared to a non-pregnant cohort with pHPT. Evidence in the published literature is explored via a review on pHPT and pregnancy outcomes.ResultsSeventeen pregnant women and 247 age range-matched non-pregnant women with pHPT were referred for surgery over 11 years. Serum calcium was higher in the pregnant cohort 2.89mmol/l vs 2.78mmol/l (p=0.03). Pre-operative localisation with ultrasound succeeded in 8(47%) pregnant women and SestaMIBI in 2/6(33% imaged pre-conception) compared to 84(34%) and 102(42%) controls (NS at 0.36 and 0.59). Parathyroidectomy was performed under general anaesthesia between 12 and 28 weeks gestation, with no adverse pregnancy outcomes resulting. Cure rate was 100% vs 96% in controls.ConclusionspHPT in pregnancy is a threat to mother and child. Medical management may be appropriate in mild disease (serum calcium <0.25mmol/l above the normal range) but in moderate-severe disease, parathyroidectomy under general anaesthesia in the second trimester is safe. Localisation using ionising radiation/MRI is unnecessary as surgical intervention in a high-volume multi-disciplinary setting has excellent outcomes. Guidelines on the topic would assist clinicians in this complex decision-making process.